Емоційне вигорання у жінок, які виховують дитину з особливостями розвитку - Грицюк, Ірина Михайлівна; Hrytsiuk, Iryna M. (Східноєвропейський національний університет імені Лесі Українки, 2015)
У статті ми розкрили особливості протікання синдрому емоційного вигорання у жінок, які виховують неповносправну дитину. Та узагальнили найважливіші фактори, які допоможуть подолати негативні емоційні чинники, та налагодити гармонійні стосунки з дитиною та оточуючими людьми.

Describing burnout as a specific psychophysical aspect, we review it as a formation of a block in emotional sphere. It occurs due to the lack of emotional adjustment to the situation in which the woman remains. Emotionally complicated situation which a woman faces having born a “special needs” child, causes accumulation of frustration, etc. The burnout comes amid fatigue, psychological deterioration and exhaustion, soreness, psychosomatic illnesses, moodiness, and insensibility. A mother that experiences burnout suffers from not being able or is ashamed to show negative emotions – anger, disappointment, irritation, fear, or the combination of these emotions. Additionally, a woman may be overwhelmed with a feeling of shame for her emotional upheaval, feeling of guilt, helplessness. When this occurs, psychological defence mechanisms arise, and the person starts to blame others for everything happening to her and tries to shuffle off the responsibility on the surrounding people’s shoulders. Everyone can work out their own strategy to fight against the burnout syndrome, but it is necessary to name some of universal rules: the rule of distribution, the change of activity rule, the rule of time, and the rule of internal metaphor. Psychologists also note a positive role of animals, which is that animals take the pressure and negative emotions off, impacting on the personality. Many scientific researches mention that interacting with animals broadens children’s sense experience, their world view, and has a positive impact on mental development in a positive way. Besides, there are data showing the improvement of family atmosphere. Practicians, mental specialists and psychologists also point out a positive impact of animals on the formation of the personality and its emotional condition, which has led to creating a specific form of mental therapy using domestic animals, became known as animal-assisted therapy.
Burnout experienced by women who raise a special needs child
Keywords: синдром емоційного вигорання; емоційна сфера; емоційні блоки; психічне виснаження; психотравмуюча обставина; анімалотерапія; особистісна деформація